Public relations leaders as sensemakers a global study of leadership in public relations and communication management - Berger, Bruce K.; Meng, Huan (New York Routledge, 2014)
"Public Relations Leaders as Sensemakers presents foundational research on the public relations profession, providing a current and compelling picture of expanding global practice. This volume is appropriate for graduate and advanced undergraduate students in international public relations and communication management, as well as scholars in global public relations, communication management, and business. It is also intended to supplement courses in public relations theory, strategic communication, business management, and leadership development"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Public relations consultants; Public relations firms; Public relations; Leadership